2013
DOI: 10.1038/leu.2013.291
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA187 overexpression is related to tumor progression and determines sensitivity to bortezomib in peripheral T-cell lymphoma

Abstract: MicroRNAs (miRs) are involved in tumorigenesis by regulating tumor suppressor genes and/or oncogenes. MiR187 was overexpressed in peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) and associated with high Ki67 expression, elevated lactate dehydrogenase, advanced International Prognostic Index and poor prognosis of patients. In vitro, ectopic expression of miR187 in T-lymphoma cell lines accelerated tumor cell proliferation, whereas treatment with miR187 inhibitor reduced cell growth. MiR187 downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
0
25
1
Order By: Relevance
“…For the first time, we demonstrated that DOX caused a higher expression of miR-187-3p in human cardiomyocytes. Notably, miR-187-3p overexpressing T-lymphoma cells show resistance to DNA damaging agents such as DOX, cisplatin and cyclophosphamide (Yan et al 2014). Thus, we may assume that miR-187-3p overexpression in cardiomyocytes is the result of DOX-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, we demonstrated that DOX caused a higher expression of miR-187-3p in human cardiomyocytes. Notably, miR-187-3p overexpressing T-lymphoma cells show resistance to DNA damaging agents such as DOX, cisplatin and cyclophosphamide (Yan et al 2014). Thus, we may assume that miR-187-3p overexpression in cardiomyocytes is the result of DOX-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, explanations involving other biological mechanisms cannot be ruled out. 7 Although standard prognostic indices for this series (International Prognostic Index and Prognostic Index for PTCL-u) identified prognostic subgroup of patients (both indices, P , .001), the mutational status of the RHOA gene did not, either in the total group of all patients or after histologic subclassification (AITL vs PTCL-NOS) ( Table 1 and supplemental Tables 2-3 available on the Blood Web site. ).…”
mentioning
confidence: 99%
“…MYC is known to be activated by the loss of SNF5 (SMARCB1), 2 overexpression of microRNA187, 5 and by its own gene amplification or translocation, thereby favoring the rapid appearance of T-cell neoplasms in humans.…”
mentioning
confidence: 99%